Comparison of global and local optimization methods for the calibration and sensitivity analysis of a conceptual hydrological model - Mendez-Morales, Maikel (2019)
Eight global and eight local optimization methods were used to calibrate the HBV-TEC hydrological model on the upper Toro river catchment in Costa Rica for four different calibration periods (4, 8, 12 and 16 years). To evaluate their sensitivity to getting trapped in local minima, each method was tested against 50 sets of randomly-generated initial model parameters. All methods were then evaluated in terms of optimization performance and computational cost. Results show a comparable performance among various global and local methods as they highly correlate to one another. Nonetheless, local methods are in general more sensitive to getting trapped in local minima, irrespective of the duration of the calibration period. Performance of the various methods seems to be independent to the total number of model calls, which may vary several orders of magnitude depending on the selected optimization method. The selection of an optimization method is largely influenced by its efficiency and the available computational resources regardless of global or local class.